T-test for two dependent samples - some practical notes - Erika Liptaková (Matej Bel University, 2021)
This paper focuses on some important issues of the t-test for two dependent samples (paired t-test). Emphasis is placed on the assumptions of the use of the test, on the correct formulation of the tested hypotheses and on the selection of the correct method in testing the averages of differences in pairwise observations. This is extended by the calculation of the confidence interval for the mean difference and calculation of the effect size by Cohend´s d. The paper also offers a demonstration of two different solutions for the same example by means of correctly and incorrectly chosen statistical test. DOI: https://doi.org/10.24040/sjss.2021.7.1.48-55